2016
DOI: 10.5146/tjpath.2016.01368
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin lymphoma in a case of chronic myeloid leukemia treated with tyrosine kinase inhibitors

Abstract: Chronic myeloid leukemia (CML) is characterized by increased and unregulated proliferation of granulocytic lineage in the bone marrow and presence of these immature myeloid cells in the peripheral blood with presence of Philadelphia (Ph) chromosome. Tyrosine kinase inhibitors are the most important drugs in the CML therapy and provide long disease-free survival. Due to the increased survival of CML patients with continual administration of these drugs, the chance of development of secondary malignancies may in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Table 1 showed the detailed clinical course of lymphomas that developed during TKI treatment in CML patients. [10][11][12][13][14][15][16][17] Among them, imatinib was the most commonly used medication, while there were no reports of patients who were treated with bosutinib. The time from the initial TKI dose to the onset of the secondary cancer was longest in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 showed the detailed clinical course of lymphomas that developed during TKI treatment in CML patients. [10][11][12][13][14][15][16][17] Among them, imatinib was the most commonly used medication, while there were no reports of patients who were treated with bosutinib. The time from the initial TKI dose to the onset of the secondary cancer was longest in our case.…”
Section: Discussionmentioning
confidence: 99%
“…On review of literature, it is studied that CML is one of the risk factors for the occurrence of other cancers (solid and hematological) secondary to bcr-abl aberrations [8]. Bcr-abl gene arises due to the translocation of the gene between long arm of chromosome 9 to chromosome 22.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the Philadelphia chromosome (the hallmark of CML). Gajendra et al suggested that this bcr-abl aberration has the potential to give rise to other malignancies due to genetic instability and clonal evolution [8]. Yap et al proposed the concept of tumor heterogeneity and sub-clonal evolution and compared this tumor heterogeneity with the growing tree model [9].…”
Section: Discussionmentioning
confidence: 99%
“…Sasaki K et al reported 31 (0.2%) CML patients with secondary lymphoma, but their clinical courses are unknown. Table 1 showed the detailed clinical course of lymphomas that developed during TKI treatment in CML patients [10][11][12][13][14][15][16][17] . Among them, imatinib was the most commonly used medication, while there were no reports of patients who were treated with bosutinib.…”
Section: Discussionmentioning
confidence: 99%